A synonymous mutation in PI4KA impacts the transcription and translation process of gene expression - Zhang, Kaihui; Kang, Lili; Zhang, Haozheng; Bai, Lu; Pang, Huanping; Liu, Qinghua; Zhang, Xinyi; Chen, Dong; Yu, Haihua; Lv, Yuqiang; Gao, Min; Liu, Yi; et al. (Frontiers in Immunology, 2022)
PI4KIIIα (phosphatidylinositol-4-kinase alpha) encoded by PI4KA gene, could synthesizing phosphatidylinositol-4-phosphate (PI-4-P), which serve as specific membrane markers and are instrumental in signal transduction. PI4KA gene mutation could Cause autosomal recessive diseases involving in neurological, intestinal and immunological conditions (OMIM: 619621, 616531, 619708). We have detected one neonatus with sepsis, severe diarrheal and decreasing immunoglobulin. Two novel compound heterozygous mutations, c.5846T>C (p.Leu1949Pro) and c.3453C>T (p.G1151=) were identified from the father and mother respectively. Sanger sequencing and RT-PCR for Peripheral blood and minigene splicing assay had both shown a deletion of 5 bases (GTGAG) with c.3453C>T variant in the mRNA level. Meanwhile, the missense mutation c.5846T>C (p.Leu1949Pro) kinase activity have been measured and little even no catalytic activity were detected. According to the clinical characteristic and gene mutations with functional verification, our pediatricians finally have diagnosed the child as combined immunodeficiency with intestinal disorder close to GIDID2 (OMIM: 609332). The medicine such as the immunomodulators was prescribed to balance the immune dysregulation. The study is the first report regarding a synonymous mutation of PI4KA gene influencing the alternative splicing. Our findings expanded the mutation spectrum leading to PI4KIIIa deficiency related diseases and provided exact information for genetic counseling.